Phytochemical Profiling of H. durvillei Ethanol Extract and the Potential Activity as Antibacterial Agents on Fish - Akbar, Said Ali; Hasan, Muhammad; Afriani, Sari; Nuzlia, Cut (Asia-Pacific Journal of Science and Technology, 2025)
The investigation into seaweed species for the extraction of bioactive compounds has gained significant importance due to its wide-ranging potential applications. This study aimed to assess the metabolite profiles and phytochemical content of Halymenia durvillei ethanol extract along the coastline of Banda Aceh, Indonesia. The methodology proposed in this research encompassed three main steps: analysis of phytochemical composition, evaluation of antioxidant scavenging activity, and in vivo metabolite profiling utilizing gas chromatography-mass spectrometry (GC-MS), Fourier-transform infrared (FTIR) spectroscopy, and the 2,2-diphenylpicrylhydrazyl (DPPH) assay. The utilization of DPPH for assessing antioxidant potential revealed significant scavenging activity, with inhibition values reaching 47.22%. GC-MS analysis demonstrated its efficacy in swiftly and accurately monitoring both individual components and overall chemical composition of H. durvillei ethanol extract. The study identified 26 phytochemical compounds within H. durvillei. Subsequently, the ethanol extract underwent FTIR spectroscopic analysis, revealing prominent peaks at 3352 cm−1, 1654 cm−1, and 1019 cm−1, indicating the presence of alkanes, alkenes, and hydroxyl groups, with other connections ranging from weak to medium. Based on the GC-M S results and literature studies, there are numerous bioactive compounds contained in H. durvillei ethanol extract that have potential as antibacterials in humans and animals, including fish. Consequently, H. durvillei exhibits promise as a source of antibacterial agents, particularly in the context of aquaculture for fish.